Analysis of the load on the knee joint and vertebral column with changes in squatting depth and weight load - Hartmann, H.; Wirth, K.; Klusemann, M. (Sports Medicine, 2013)
It has been suggested that deep squats could cause an increased injury risk of the lumbar spine and the knee joints. Avoiding deep flexion has been recommended to minimize the magnitude of knee-joint forces. Unfortunately this suggestion has not taken the influence of the wrapping effect, functional adaptations and soft tissue contact between the back of thigh and calf into account. The aim of this literature review is to assess whether squats with less knee flexion (half/quarter squats) are safer on the musculoskeletal system than deep squats. A search of relevant scientific publications was conducted between March 2011 and January 2013 using PubMed. Over 164 articles were included in the review. There are no realistic estimations of knee-joint forces for knee-flexion angles beyond 50° in the deep squat. Based on biomechanical calculations and measurements of cadaver knee joints, the highest retropatellar compressive forces and stresses can be seen at 90°. With increasing flexion, the wrapping effect contributes to an enhanced load distribution and enhanced force transfer with lower retropatellar compressive forces. Additionally, with further flexion of the knee joint a cranial displacement of facet contact areas with continuous enlargement of the retropatellar articulating surface occurs. Both lead to lower retropatellar compressive stresses. Menisci and cartilage, ligaments and bones are susceptible to anabolic metabolic processes and functional structural adaptations in response to increased activity and mechanical influences. Concerns about degenerative changes of the tendofemoral complex and the apparent higher risk for chondromalacia, osteoarthritis, and osteochondritis in deep squats are unfounded. With the same load configuration as in the deep squat, half and quarter squat training with comparatively supra-maximal loads will favour degenerative changes in the knee joints and spinal joints in the long term. Provided that technique is learned accurately under expert supervision and with progressive training loads, the deep squat presents an effective training exercise for protection against injuries and strengthening of the lower extremity. Contrary to commonly voiced concern, deep squats do not contribute increased risk of injury to passive tissues.